GROUNDWATER IRRIGATION AND ITS IMPLICATIONS FOR WATER POLICY IN SEMIARID COUNTRIES: THE SPANISH EXPERIENCE - Garrido A.; Martínez-santos P.; Llamas M.R. (My University, 2006)
Over the last decades, groundwater irrigation has become commonplace in many arid and semiarid regions worldwide, including Spain. This is largely a consequence of the advances in drilling and pumping technologies, and of the development of Hydrogeology. Compared with traditional surface water irrigation systems, groundwater irrigation offers more reliable supplies, lesser vulnerability to droughts, and ready accessibility for individual users. Economic forces influence the groundwater irrigation sector and its development. In Spain's Mediterranean regions, abstraction costs often amount to a very small fraction of the value of crops. In the inner areas, groundwater irrigation supports a more stable flow of farm income than rainfed agriculture. The social (jobs/m3) and economic (€/m3) value of groundwater irrigation generally exceeds that of surface water irrigation systems. However, poor groundwater management and legal controversies are currently at the base of Spain's social disputes over water. A thorough and transparent assessment of the relative socio-economic value of groundwater in relation to surface water irrigation might contribute to mitigate or avoid potential future conflicts. Enforcement of the European Union's Water Framework Directive may deliver better groundwater governance and a more sustainable use.
Keywords: IRRIGATION; GROUNDWATER MANAGEMENT; GROUNDWATER ECONOMICS; WATER POLICY; SPAIN